An Exploration of Work Anxiety, Adaptability, and Help-Seeking Barriers among University Faculty during the Pandemic - Crisostomo, Agnes; Tigno, Ma. Adora; Ranas, Estrella; Ochoa, Josefina (Journal of Interdisciplinary Perspectives, 2025)
The Covid-19 pandemic has profoundly impacted the education sector, especially teachers' psychological well-being. This study investigates anxiety, adaptability, and barriers to help-seeking behaviors among 468 Central Luzon teachers from state universities and colleges (SUCs). It also examines the relationships among these variables. Using a mixed-methods approach, quantitative data were gathered through an online survey, while qualitative insights were obtained from a virtual focus group discussion with seven participants. Results indicate that teachers experienced high anxiety levels (M=3.59), driven by health concerns, technology-related challenges, and transportation issues. Despite these stressors, their adaptability to work was also high (M=3.6), supported by coping strategies such as self-care, seeking support, and acceptance. However, moderate barriers to seeking professional help (M=3.0) were identified, linked to self-reliance, social stigma, and faith. The study further reveals that difficulties in seeking mental health support are associated with lower adaptability at work. These findings emphasize the importance of promoting self-care practices and resilience-building initiatives for SUC faculty during and beyond the pandemic.